Perlindungan Konsumen Terhadap Penipuan yang dilakukan Broker Forex Ilegal - I Made Aswin Ksamawantara; Johannes Ibrahim Kosasih; I Made Minggu Widyantara (Fakultas Hukum, Universitas Warmadewa, 2021)
The phenomenon of Foreign Exchange (Forex) that runs in the investment sector and can help the development of Indonesia. Currently forex is a trend that is endemic and attracts the attention of many parties, both investors and the public in general. Foreign exchange or forex is a type of trade or transaction that trades the currency of a country against the currencies of other countries involving the main money markets in the world for 24 hours continuously, so in this case a legal protection is needed. The purpose of this research is to analyze legal protection in Forex transactions and legal sanctions imposed by the government on illegal Forex broker activities. This research uses a normative method that with a statutory approach. Sources of data used are primary data sources and secondary data sources. After primary legal data and secondary legal data are collected, the data will then be processed and analyzed using systematic legal data processing methods. The results showed that the alleged fraudulent investment fraud case under the guise of forex trading involved illegal brokers from the Guardian Capital Group (GCG) Asia, which harmed consumers. In line with that, the government issued a legal rule, namely Law No.8 of 1999 concerning Consumer Protection. The Consumer Protection Law that has been set by the government is the legal basis that is accurate and full of optimism in protecting consumer rights.